2018
DOI: 10.1002/jcp.27104
|View full text |Cite
|
Sign up to set email alerts
|

Specific neural phase relation of serotonin and dopamine modulate the testicular activity in Japanese quail

Abstract: Specific phase relation of serotonin and dopamine modulate the hypothalamo-hypophyseal-gonadal axis as well as photosexual responses in Japanese quail, but the effect of these specific phase relations on testicular activity and steroidogenesis is not yet been investigated. We hypothesized that temporal phase relation induced alteration in local testicular gonadotropin-releasing hormone (GnRH)-Gonadotropin-inhibitory hormone (GnIH) and their receptor system may modulate the testicular activity and steroidogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…However, before concluding this and validating the earlier ideas, we must consider the specificity and sensitivity of the techniques that we have used. Although histochemistry may be considered an old method, this analysis has been used to identify not only 5-HT but also adrenaline, noradrenaline, and dopamine in testes, raising the possibility that other neurotransmitters could directly participate in the regulation of spermatogenesis in adult rats (Meizel, 2004;Hökfelt, 2010;Banerjee and Chaturvedi, 2019). The monoclonal antibodies against 5-HT that we used did not allow us to exclude the possibility of the presence of another indolamine, i.e., evidence of the local synthesis of melatonin in rat testes has been reported (Tijmes et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, before concluding this and validating the earlier ideas, we must consider the specificity and sensitivity of the techniques that we have used. Although histochemistry may be considered an old method, this analysis has been used to identify not only 5-HT but also adrenaline, noradrenaline, and dopamine in testes, raising the possibility that other neurotransmitters could directly participate in the regulation of spermatogenesis in adult rats (Meizel, 2004;Hökfelt, 2010;Banerjee and Chaturvedi, 2019). The monoclonal antibodies against 5-HT that we used did not allow us to exclude the possibility of the presence of another indolamine, i.e., evidence of the local synthesis of melatonin in rat testes has been reported (Tijmes et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggested that OPN5 played an important role in the regulation of avian reproductive activity by mediating photoperiod in non-seasonal breeding avian. OPN5 affects TSH, which activates the DIO2/DIO3 conversion system ( Ono et al, 2008 ), which in turn affects the GnRH/GnIH system and the GnRHR/GnIHR system, altering the expression of related reproductive genes and causing changes in the corresponding reproductive hormones, thus regulating the ovarian functional system ( Banerjee and Chaturvedi, 2018 ). Furthermore, OPN5 has been shown to mediate light signaling and cause a drift in rhythmic phase, which in turn is involved in the regulation of animal biological rhythms and reproductive functions, such as the association of altered sexual behavior and GnRH release ( Prasad et al, 2015 ; Han et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone treatment in some studies is showed a strong influence on SERT expression (Kranz et al, 2015), whereas our data are almost absent in S-to-L groups and only reduced SERT expression in L-to-S groups. Several studies concerned with the association of neurotransmitters, especially serotonin, with seasonal reproduction have been reported (Lambert et al, 2002;Banerjee and Chaturvedi, 2019). Moreover, numerous studies have found that steroidogenesis is closely associated with seasonal reproduction, but the correlations between neurotransmitter and steroidogenesis are still unclear.…”
Section: Discussionmentioning
confidence: 99%